Similar and Shared Nongenomic Mechanisms of Action of Estrogen and Thyroid Hormone - Davis, Faith B.; Lin, Hung-Yun; Luidens, Mary K.; Zhou, Min; Mousa, Shaker A. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2009)
Thyroid hormone and estrogen have nongenomic, as well as genomic, mechanisms of action. Some of these nongenomic actions of thyroid hormone and estrogen are similar or identical. For example, transduction mechanisms of thyroid hormone and estradiol signals at discrete plasma membrane hormone-binding sites of breast cancer cells, but both then utilize activation of mitogen-actrivated protein kinase (MAPK), depend upon MAPK-requiring phosphorylation of serine-118 of the nuclear estrogen receptor (ER)-α and culminate in genomically-directed, ER-dependent breast cancer cell proliferation. In this review, several mechanisms of action of estrogen and thyroid hormone are discussed that are initiated nongenomically, but, downstream of initiation sites are similar or shared. Some of these effects end genomically. The actions include hormone-directed angiogenesis, modulation of activities of plasma membrane ion transporters, regulation of the state of the actin cytoskeleton and stimulation of cancer cell proliferation, including breast and, surprisingly, thyroid cancer.
Keywords: Thyroxine